We Really Need Clear Guidelines and Recommendations for Safer and Proper Use of Aripiprazole and Risperidone in a Pediatric Population: Real-World Analysis of EudraVigilance Database - Rafaniello, Concetta; Sullo, Maria Giuseppa; Carnovale, Carla; Pozzi, Marco; Stelitano, Barbara; Radice, Sonia; Bernardini, Renato; Rossi, Francesco; Clementi, Emilio; Capuano, Annalisa (Frontiers in Psychiatry, 2020)
Background: Although aripiprazole and risperidone are used widespread in pediatrics, there are still limited pieces of evidence on their actual safety profile. By using the EudraVigilance database, we carried out an analysis to perform a comprehensive overview of reported adverse events among children and adolescents treated with aripiprazole and risperidone. Methods: Descriptive analysis was performed of all individual case safety reports (ISCRs) submitted to EudraVigilance associated with aripiprazole and risperidone and related to the pediatric population from 2016 to 2018. Results: A total of 855 and 2,242 ISCRs for aripiprazole and risperidone, respectively, were recorded for a total of 11,042 suspected adverse drug reactions (2,993 for aripiprazole and 8,049 for risperidone). Most ISCRs were related to male patients (65.0 and 86.3% for aripiprazole and risperidone, respectively) and were serious (81.0 and 94.1% for aripiprazole and risperidone, respectively). Schizophrenia spectrum and other psychotic disorders, such as disruptive, impulse-control, and conduct disorders, and autism spectrum disorder were the top three clinical indications for aripiprazole (19.0, 16.1, and 11.6%, respectively). For risperidone, attention-deficit/hyperactivity disorder (25.4%), disruptive, impulse-control, and conduct disorders (17.1%), and bipolar and related disorders (14.2%) were more commonly reported as clinical indications. Data also showed a high proportion of use for clinical conditions not authorized in children. Psychiatric disorders were the main related adverse events for aripiprazole (20.2%), and among these, suicidal behavior was one of the most reported (14.9%). Reproductive system and breast disorders were the main related adverse events for risperidone (19.8%), and gynecomastia was the most reported event; metabolism and nutrition disorders, mainly reported as weight gain disorders, were more reported in children (3–11 years) than in adolescents (12–17 years). Conclusions: Our results demonstrate that spontaneously reported adverse events associated with aripiprazole and risperidone reflect what is already known in terms of safety profile, although with about 90% of them being serious. This analysis stresses the need for further studies and effective training and information activities to better define the actual benefit/risk ratio of these drugs in pediatric patients.